Drosophila as a model system for deciphering the 'host physiology-nutrition-microbiome' axis. - Lee, J.H.; Lee, K.A.; Lee, W.J. (Current opinion in insect science, 2020)
For metazoans, nutritional stressors, such as undernutrition during growth and development, results in serious outcomes, including growth impairments and organ wasting. When undernutrition is accompanied by other complications, including chronic inflammation, a more complex pathophysiology may emerge, such as environmental enteropathy. Although nutrition is one of the most important environmental factors that influences host physiology, the mechanism by which undernutrition induces host pathophysiology is not fully understood. Recently, gut microbiome was found to alleviate undernutrition-induced pathophysiology in an insect model, revealing the importance of nutrition-microbiome interactions. Here, we discussed how nutrition-microbiome interactions influence host physiology, including growth, tissue homeostasis, immunity, and behavior, by regulating the central metabolic signaling pathways with an emphasis on findings made through Drosophila, an insect model.